Masculinization of Tilapia (Oreochromis niloticus) Using Methyl Testosterone Natural Hormone - Rosmaidar R; Winaruddin W; Mimi Herlina (Jurnal Medika Veterinaria, 2014)
This study aimed to determine the effect of methyl testosterone natural hormoneon the rate of masculinization of tilapia (Oreochromis niloticus). The study used 270 tilapia larvae with the age of 7 days as experimental animals. Tilapia larvae were divided into 3 treatments; eachtreatment consisted of 30 larvae fish. This study was an experimental study using completely randomized design with 3 treatments and 3replications. Treatment I as control group was fed with pellets ad libitum, treatment II was given feed containing methyl testosterone naturalhormone, and treatment group III was given hormone treatment by soaking the fish larvae with methyl testosterone natural hormone for 20hours. Larvae were raised in accordance with applicable procedures. Observation was conducted when the larvae fish were at 60 days old andthe sex of fish can be observed. Parameter examined was the percentage of the male sex. The average (± SD) percentage of male tilapia in groupPI, PII, and PIII were 36.39±3.97, 66.72±6.13, and 82.37±6.87%, respectively. The results showed that the percentage of male sex of tilapia fedwith natural hormone of methyl testosterone through the diet and dipping was significantly different (P0.05) from control fish. In conclusion,the administration of natural hormone of methyl testosterone increased the percentage of the male sex of tilapia).____________________________________________________________________________________________________________________Key words: tilapia larvae, natural hormone methyl testosterone, the male sex percentage